2015
DOI: 10.1371/journal.pone.0135790
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sound Localization Strategies in Children with Bilateral Cochlear Implants

Abstract: Localizing sounds in our environment is one of the fundamental perceptual abilities that enable humans to communicate, and to remain safe. Because the acoustic cues necessary for computing source locations consist of differences between the two ears in signal intensity and arrival time, sound localization is fairly poor when a single ear is available. In adults who become deaf and are fitted with cochlear implants (CIs) sound localization is known to improve when bilateral CIs (BiCIs) are used compared to when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 45 publications
6
59
1
Order By: Relevance
“…Similar differences between CI users and NH children were found by van Deun and colleagues[6]. More recently Zheng and colleagues [7] investigated emergence of sound localization skills in a group of 19 bilaterally implanted children, and reported that with additional experience listening through BiCIs, most children improve, as seen in reduced localization errors. The error types were further analyzed to better understand whether the pattern of errors change with experience.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar differences between CI users and NH children were found by van Deun and colleagues[6]. More recently Zheng and colleagues [7] investigated emergence of sound localization skills in a group of 19 bilaterally implanted children, and reported that with additional experience listening through BiCIs, most children improve, as seen in reduced localization errors. The error types were further analyzed to better understand whether the pattern of errors change with experience.…”
Section: Introductionsupporting
confidence: 65%
“…Of the 20 children tested here, 11 were also tested on localization as reported by Zheng and colleagues [7], and for those children some comparisons are made between the speech-in-noise data and the localization results. This study sought to determine whether children demonstrate improvement on speech reception thresholds (SRTs), and/or on their ability to benefit from spatial separation of the target and interferers.…”
Section: Introductionmentioning
confidence: 99%
“…RMS localization errors are also generally better in the bilateral condition compared with the unilateral condition (GriecoCalub and Litovsky, 2010). However, even when using BiCIs, these children show significantly poorer performance compared to their NH age-matched peers; this gap in performance is observed even after several years of experience with BiCIs (Zheng et al, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…For recent reviews on this topic see also [5, 6]. A second measure is localization accuracy, which is informative regarding the ability of a listener to identify the location of a sound source from amongst an array of sources; accuracy can be measured for sound sources along the vertical or horizontal dimension but in bilateral CI users the focus has been on the horizontal plane, where binaural cues would be most effectively utilized [11]. Figure 1 summarizes data from recent studies in which acuity and accuracy were measured in children with bilateral CIs.…”
Section: Spatial Hearing In Bilaterally Implanted Childrenmentioning
confidence: 99%